A teatralidade na performance percussiva: uma abordagem criativa - Aquim de Souza Lopes Almeida (2023)
This research proposes to apply the concept of Theatricality in Percussive Performance, in a creative approach. Therefore, in the first chapter, we explore the concepts of performance based on theoretical material from Schechner, Féral, Fernandes and other authors. From there, we deepened the concept of Performance as an artistic expression in order to draw a parallel between the happening, body art, action painting and performance art and three works of the percussive repertoire: Living Room Music, Dressur and Vice Versa. Having understood the place of percussive performance and understanding the existence of this relationship between Performance and Theatricality, we focus on the concept of Theatricality, something still little visited in music, to observe possible common and parallel characteristics to combine with the construction of the performance of the repertoire written for percussion instruments , seeking to understand to what extent the application of this content can influence this practice of percussive performance by bringing new elements to this performative construction. For this, we will focus on observing some elements of Theatricality in different artistic expressions, to, in a subsequent moment, observe elements of this concept in gestural and corporal aspects of the percussionist in his performance. Finally, in the third chapter, we apply this concept to four works of the percussive repertoire, through a self-creative approach: Omar, The Source, Coquim – Saudade das Laranjeiras and Oxóssi, with ways to illustrate the results that can be obtained in a percussive performance through this conceptual relationship.